Using whole genome sequencing to characterize Clostridioides difficile isolates at a tertiary center in Melbourne, Australia - Alice Liu; Eddie Chan; Victoria Madigan; Vivian Leung; Lucille Dosvaldo; Norelle Sherry; Benjamin Howden; Katherine Bond; Caroline Marshall (Cambridge University Press, 2024)
Abstract Objective: Clostridioides difficile infection (CDI) is the commonest cause of healthcare-associated diarrhea and undergoes standardized surveillance and mandatory reporting in most Australian states and territories. Historically attributed to nosocomial spread, local and international whole genome sequencing (WGS) data suggest varied sources of acquisition. This study describes C. difficile genotypes isolated at a tertiary center in Melbourne, Australia, their likely source of acquisition, and common risk factors. Design: Retrospective observational study. Setting: The Royal Melbourne Hospital (RMH), a 570-bed tertiary center in Victoria, Australia. Methods: Short-read whole genome sequencing was performed on 75 out of 137 C. difficile isolates obtained from 1/5/2021 to 28/2/2022 and compared to previous data from 8/11/2015 to 1/11/2016. Existing data from infection control surveillance and electronic medical records were used for epidemiological and risk factor analysis. Results: Eighty-five (62.1%) of the 137 cases were defined as healthcare-associated from epidemiological data. On genome sequencing, 33 different multi-locus sequence type (MLST) subtypes were identified, with changes in population structure compared to the 2015-16 period. Risk factors for CDI were present in 130 (94.9%) cases, including 108 (78.8%) on antibiotics, 86 (62.8%) on acid suppression therapy, and 25 (18.2) on chemotherapy. Conclusion: In both study periods, most C. difficile isolates were not closely related, suggesting varied sources of acquisition and that spread of C. difficile within the hospital was unlikely. Current infection control precautions may therefore warrant review. Underlying risk factors for CDI were common and may contribute to the proportion of healthcare-associated infections in the absence of proven hospital transmission.